2020
DOI: 10.1186/s12882-020-01861-2
|View full text |Cite
|
Sign up to set email alerts
|

Brilliant blue G, a P2X7 receptor antagonist, attenuates early phase of renal inflammation, interstitial fibrosis and is associated with renal cell proliferation in ureteral obstruction in rats

Abstract: Background: Previous study showed that purinergic P2X7 receptors (P2X7R) reach the highest expression in the first week after unilateral ureteral obstruction (UUO) in mice, and are involved in the process of inflammation, apoptosis and fibrosis of renal tissue. We, herein, document the role of purinergic P2X7 receptors activation on the third day of UUO, as assessed by means of BBG as its selective inhibitor. Methods: We investigated the effects of brilliant blue G (BBG), a P2X7R antagonist, in the third day o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
(48 reference statements)
1
9
1
Order By: Relevance
“…Our experiments in both T1D and T2D podocytes with specific inhibitors provide compelling evidence that P2X 4 and P2X 7 receptors play a major role in ATP-induced [Ca 2+ ] i levels in diabetic podocytes. Previous research has established that P2X 7 receptor expression increases are linked to PKD, glomerulonephritis, human lupus nephritis, and hypertension-associated renal injury ( Arkhipov et al., 2019 ; Hillman et al., 2005 ; Pereira et al., 2020 ; Vallon et al., 2020 ). In addition, the upregulation of glomerular P2X 7 receptor mRNA and protein expression has been reported in STZ-induced diabetic and ren-2 transgenic hypertensive rat models, and was associated with inflammatory cytokine release and cell death ( Vonend et al., 2004a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experiments in both T1D and T2D podocytes with specific inhibitors provide compelling evidence that P2X 4 and P2X 7 receptors play a major role in ATP-induced [Ca 2+ ] i levels in diabetic podocytes. Previous research has established that P2X 7 receptor expression increases are linked to PKD, glomerulonephritis, human lupus nephritis, and hypertension-associated renal injury ( Arkhipov et al., 2019 ; Hillman et al., 2005 ; Pereira et al., 2020 ; Vallon et al., 2020 ). In addition, the upregulation of glomerular P2X 7 receptor mRNA and protein expression has been reported in STZ-induced diabetic and ren-2 transgenic hypertensive rat models, and was associated with inflammatory cytokine release and cell death ( Vonend et al., 2004a ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the upregulation of glomerular P2X 7 receptor mRNA and protein expression has been reported in STZ-induced diabetic and ren-2 transgenic hypertensive rat models, and was associated with inflammatory cytokine release and cell death ( Vonend et al., 2004a ). Studies have also shown that pharmacological inhibition or deletion of P2X 7 receptor offers varying degrees of protection in these pathologies ( Arkhipov et al., 2019 ; Ji et al., 2012 ; Menzies et al., 2015 , 2017a , 2017b ; Pereira et al., 2020 ; Taylor et al., 2009b ). Here we show that podocytes in late-stage diabetes mellitus have direct ionotropic P2 calcium entry through the pore-forming P2X 4 , and P2X 7 channels in addition to metabotropic signaling through P2Y 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies indicate that the activation of P2X7Rs in macrophages is involved in peripheral inflammatory diseases, including rheumatoid arthritis [ 53 ], Crohn’s disease [ 108 ], liver fibrosis [ 109 , 110 ], sepsis [ 101 , 111 ], renal inflammation [ 112 , 113 ], and pulmonary inflammation [ 114 ]. Almost all peripheral inflammatory diseases share the same, classic inflammatory pathway in macrophages with the following components: P2X7R stimulation, NLRP3 and caspase-1 activation, and IL-1β/IL-18 release.…”
Section: Peripheral Inflammatory Diseasesmentioning
confidence: 99%
“…P2X7 receptor is an ATP-gated purinergic ion channel widely present in different cells and tissues, such as stem cells [ 1 ], brain [ 2 ], intestine [ 3 ], kidney [ 4 ] and mostly expressed in immune [ 5 ] and several cancer cells [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%